Bureaucracy: Major Barrier for Payment to Contractors in Nigeria - Umar, Garba Maiunguwa (School of Social Sciences, 2015)
This paper titled “Bureaucracy: major barrier for payment to contractors in Nigeria” intends to investigate the payment procedure of public construction projects in Nigeria. Payments problems are old age issues that permeate the Nigerian construction industry. Many a times, contractors and other parties down the supply chain complain either they are not been paid or payments have been unduly delayed by the client. A literature study was carried out to ascertain the state of payment procedure in Nigeria. The payment procedure of Nigeria is compared with that of Scotland and this is because Nigeria is adapting the conditions of contract being practice in UK. The findings of the study reveals that government bureaucratic procedure is contributing significantly to the late payment and nonpayment issues in the Nigerian construction industry with it associated negative consequences on projects in particular and the industry at large. The findings will be useful to the government for the review of current payment procedure through policy formulation and implementation, which will improve payment practice of public projects and by extension improve the performance of the construction industry.